Molecular Simulation Studies on Thermophysical Properties With Application to Working Fluids - Raabe, Gabriele; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book discusses the fundamentals of molecular simulation, starting with the basics of statistical mechanics and providing introductions to Monte Carlo and molecular dynamics simulation techniques. It also offers an overview of force-field models for molecular simulations and their parameterization, with a discussion of specific aspects. The book then summarizes the available know-how for analyzing molecular simulation outputs to derive information on thermophysical and structural properties. Both the force-field modeling and the analysis of simulation outputs are illustrated by various examples. Simulation studies on recently introduced HFO compounds as working fluids for different technical applications demonstrate the value of molecular simulations in providing predictions for poorly understood compounds and gaining a molecular-level understanding of their properties. This book will prove a valuable resource to researchers and students alike.
Introduction -- Introduction to Statistical Mechanics -- Monte Carlo Simulations -- Molecular Dynamics Simulations -- Running Molecular Simulations -- Molecular Models (Force Fields) -- Thermophysical and Structural Properties from Molecular Simulation -- Applications of Molecular Simulations to Studies on Working Fluids -- Conclusion and Outlook -- A Force Field Parameters.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Atomic structure .; Molecular structure .; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Atomic and Molecular Structure and Properties